Impacts of the COVID-19 pandemic on the diagnosis, care and mortality of oncological patients in Brazil: a literature review (Research, Society and Development, 2021)
The COVID-19 pandemic has severely affected healthcare systems around the world, affecting the assistance for a variety of chronic diseases, including cancer diagnosis and treatment. Cancer patients are included in the group of vulnerability to higher severity and mortality from Sars-CoV-2 infection. Studies on the impact of COVID-19 on Brazilian cancer patients are insufficient in the literature. This study aims to compile information on the impact of the COVID-19 pandemic on Brazilian cancer patients, mainly about diagnosis, care, and mortality. A literature review was carried in Google Scholar, Scielo and Pubmed platforms. The following descriptors were stablished: “COVID-19”, “Cancer”, “Mortality”, “Diagnosis” and “Service”. A total of 13 articles were included in the review. The studies analyzed involved populations from different Brazilian regions, mostly in the Southeast region. Multiple types of cancer were observed, with emphasis on head and neck neoplasms. All studies showed a reduction in the numbers of cancer diagnoses, a deficit in the number of appointments, hospitalizations and surgical procedures was also evidenced, in addition to high mortality rates for cancer patients infected by the Sars-CoV-2. In conclusion, the research demonstrated the huge impact of pandemic course on cancer patients by decreasing the number of diagnoses, appointments, surgeries, and a significant increase in the hospital mortality rate. These findings indicate the imminent negative consequences in the diagnosis and mortality from cancer in the following years and could provide warning for the development of health protocols and continuous research that minimize these impacts.